Flexible nanogenerator based on ZnO nanofiber composite material and preparation method thereof

Through heat treatment and hydrothermal growth technology, ZnO/PAN nanofiber composite piezoelectric material was prepared, which solved the problems of low electromechanical conversion capability and surface charge residue of electrospun PAN piezoelectric films, achieving more efficient and stable electrical energy conversion.

CN119465618AInactive Publication Date: 2025-02-18YANCHENG INST OF TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411598901.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The electrospun PAN piezoelectric film has low electromechanical conversion ability, and there is charge residue on the surface under the high-voltage electrostatic field, which affects the stability of the piezoelectric output.

Method used

By thermally treating and hydrothermal growth of the electrospinned Zn(Ac)2/PAN composite nanofiber membrane, ZnO/PAN nanofiber composite piezoelectric material was prepared to improve its mecha-electric conversion performance and stability.

Benefits of technology

It achieves better electromechanical conversion performance and stability, and can maintain stable electrical signal output after long-term work, suitable for wearable electronic products and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119465618A_ABST
    Figure CN119465618A_ABST
Patent Text Reader

Abstract

The invention provides a flexible nanogenerator based on a ZnO nanofiber composite material and a preparation method and application thereof, and relates to the technical field of nanogenerators. According to the preparation method, the flexible PENG based on PAN nanofibers and ZnO nanorods is prepared by combining electrostatic spinning and a low-temperature hydrothermal synthesis technology, and SEM, FTIR and XRD are adopted to characterize the morphology and the structure of the piezoelectric composite film. Compared with a single piezoelectric material, the piezoelectric material shows more excellent electro-mechanical conversion performance. In addition, after the ZnO / PAN-based PENG continuously works for more than 1500 cycles, the ZnO / PAN-based PENG still maintains a stable output electric signal. The sensor not only can be used as a pressure sensor to identify walking, running and other activity states, but also can be used as a wearable power supply to drive a heating sheet of a sole, and provides a new material for outdoor equipment development such as mountaineering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nanogenerators, and in particular to a flexible nanogenerator based on a ZnO nanofiber composite material and a preparation method thereof. Background Art

[0002] Piezoelectric nanogenerator is an energy conversion device that can effectively convert mechanical energy in the surrounding environment into electrical energy using the piezoelectric effect, and has become a major device for sustainable energy collection. As an important component of PENG, various piezoelectric materials have been studied, including ZnO, PZT, polymers, composites, and peptides. Among them, polymers and polymer composites are particularly popular in wearable electronic products due to their relatively large piezoelectric coefficients and flexibility. For example, PVDF is a widely used semi-crystalline piezoelectric polymer. In recent years, PAN has been re-studied as a piezoelectric polymer material to replace PVDF and has been used in the field of energy collection. Compared with PVDF membrane, electrospun PAN nanofiber membrane has a lower price, good thermal stability, and lower dielectric loss.

[0003] However, the electromechanical conversion capability of electrospun PAN piezoelectric films is still low, which is a challenge for the manufacture of high-efficiency power generation equipment. In addition, due to stretching and polarization under high-voltage electrostatic fields, a certain amount of charge remains on the surface of the PAN nanofiber membrane. These residual surface charges will dissipate over time, which will seriously affect the stability of the piezoelectric output of the nanofiber film. Therefore, improving the piezoelectric energy conversion efficiency of PAN nanofiber membranes and reducing the residual surface charge are of great significance for the preparation of efficient and stable energy harvesting devices. It is well known that the conformation of the polymer chain plays a decisive role in the piezoelectricity of polymer piezoelectric materials. In the solid state, the PAN macromolecular chain has two conformations, namely 3 1 -helical and planar zigzag conformations; among them, the planar zigzag conformation has a larger dipole orientation, which makes PAN piezoelectric. Usually, mechanical stretching, electric field polarization and material composite methods are used to achieve the transformation of molecular chain conformation. The piezoelectric composite material formed by inorganic and polymer piezoelectric materials can not only improve the conformation of piezoelectric polymers, but also give them the excellent properties of inorganic piezoelectric materials, broadening the application range of PENG. For example, the combination of ZnO nanomaterials and PVDF can significantly increase the content of β crystal in PVDF, thereby improving the electromechanical coupling coefficient of piezoelectric polymers. Summary of the invention

[0004] In view of this, the purpose of the present invention is to provide a flexible nanogenerator based on ZnO nanofiber composite materials and a preparation method thereof to power microelectronic devices. The present invention combines electrospinning and low-temperature hydrothermal synthesis technology to prepare a flexible PENG based on PAN nanofibers and ZnO nanorods, which exhibits better electromechanical conversion performance. In order to achieve the above-mentioned invention purpose, the present invention provides the following technical solutions:

[0005] The present invention provides a method for preparing a ZnO / PAN nanofiber composite piezoelectric material, comprising the following steps:

[0006] The electrospun Zn(Ac)2 / PAN composite nanofiber membrane was subjected to heat treatment and then further hydrothermally grown to obtain a ZnO / PAN nanofiber composite piezoelectric material;

[0007] The preparation process of the ZnO nanorod array includes the decomposition of Zn(Ac)2 and the growth of ZnO nanorods. The temperature of the oven during the heat treatment is 130±5°C and the heat treatment time is 24h. The temperature of the hydrothermal synthesis is 90±5°C and the hydrothermal growth time is 3h. When the temperature of the heat treatment is lower than 130±5°C or the temperature of the hydrothermal synthesis is lower than 90±5°C, the environment of the program heat treatment and hydrothermal synthesis is in a heated state, and the composite nanofiber membrane is avoided from being placed in an oven or growth liquid before reaching a specific treatment temperature.

[0008] Preferably, the growth solution is composed of Zn(NO3)2·6H2O, NH3·H2O, HMTA and DI. The concentration of the growth solution is 30 mM, the volume ratio of NH3·H2O is 5%, and the concentration of HMTA is 10 mM.

[0009] Preferably, the electrospun Zn(Ac)2 / PAN composite nanofiber membrane is obtained by electrospinning a Zn(Ac)2 / PAN solution;

[0010] The electrospinning process parameters include: the applied voltage of electrospinning is 22 kV, the flow rate of Zn(Ac)2 / PAN spinning solution is 0.5 mL·h -1 , the spinning distance is 15 cm.

[0011] The present invention provides a ZnO / PAN nanofiber composite piezoelectric material obtained by the preparation method described in the above technical solution.

[0012] Preferably, the thickness of the ZnO / PAN nanofiber composite piezoelectric material is about 100±10 μm.

[0013] The present invention provides the application of the ZnO / PAN nanofiber composite piezoelectric material described in the above technical solution in an electromechanical conversion device.

[0014] The present invention provides a flexible piezoelectric nanogenerator based on a ZnO nanofiber composite material, wherein the sandwich structure sequentially comprises a PET insulating layer, a copper metal electrode layer, a ZnO / PAN nanofiber composite piezoelectric material layer, a copper metal electrode layer and a PET insulating layer;

[0015] The material of the nanofiber composite piezoelectric material layer is the ZnO / PAN nanofiber composite piezoelectric material described in the above technical solution.

[0016] The present invention also provides applications of the flexible piezoelectric nanogenerator described in the above technical solution in the fields of medical care, personal thermal management and human activity monitoring.

[0017] The present invention provides a method for preparing a ZnO / PAN nanofiber composite piezoelectric material, comprising the following steps: heat-treating the electrostatically spun Zn(Ac)2 / PAN composite nanofiber membrane to obtain a ZnO seed layer / PAN composite nanofiber membrane; the temperature of the oven during the heat treatment is 130±5°C, and the heat treatment time is 24h. When the temperature of the heat treatment is lower than 130±5°C, the environment of the program heat treatment is in a heating state, and the Zn(Ac)2 / PAN composite nanofiber membrane is avoided from being placed in the oven before reaching a specific treatment temperature. When the hydrothermal synthesis temperature is lower than 90±5°C, the environment of the program hydrothermal synthesis is in a heating state, and the ZnO seed layer / PAN composite nanofiber membrane is avoided from being placed in a growth liquid before reaching a specific treatment temperature. After the Zn(Ac)2 / PAN composite nanofiber membrane prepared by the present invention is heat-treated at 130±5°C, Zn(Ac)2 undergoes thermal decomposition and is decomposed into ZnO to form a seed layer on the nanofiber; moreover, after the Zn(Ac)2 / PAN composite nanofiber membrane is heat-treated by the present invention, the composite nanofiber membrane still maintains flexibility; the hydrothermally synthesized ZnO nanorods are arranged along the fiber axis; the ZnO / PAN nanofiber composite piezoelectric material obtained by the preparation method provided by the present invention still maintains the flexibility and air permeability of the nanofiber membrane.

[0018] The present invention provides a ZnO / PAN nanofiber composite piezoelectric material obtained by the preparation method described in the above technical solution. The ZnO / PAN nanofiber composite piezoelectric material provided by the present invention has excellent electromechanical conversion performance and flexibility. As shown in the results of the embodiments of the present invention, after the ZnO / PAN nanofiber composite piezoelectric material provided by the present invention has been continuously operated for more than 1500 cycles, the ZnO / PAN-based PENG still has a stable electrical signal output, and the electrical signal does not change significantly.

[0019] The present invention provides a flexible piezoelectric nanogenerator based on a ZnO nanofiber composite material, wherein the sandwich structure sequentially comprises a PET insulating layer, a copper metal electrode layer, a ZnO / PAN nanofiber composite piezoelectric material layer, a copper metal electrode layer and a PET insulating layer; the material of the nanofiber composite piezoelectric material layer is the ZnO / PAN nanofiber composite piezoelectric material described in the above technical solution. The flexible piezoelectric nanogenerator provided by the present invention can effectively convert mechanical energy into electrical energy, and when the external resistance is 1.3MΩ, the maximum output power of the ZnO / PAN-based PENG is about 6μW. After working continuously for a long time, it still has stable electrical output performance. It can not only be used as a pressure sensor to identify the two activity states of walking and running, but also can be used as a wearable power source to drive a heating plate on the sole of the foot, showing great potential in the fields of medical care, personal thermal management and human activity monitoring. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 Schematic diagram of the preparation process and assembly of ZnO / PAN-based piezoelectric nanogenerator;

[0021] Figure 2 SEM images of PAN and ZnO / PAN nanofiber membranes;

[0022] Figure 3 The infrared spectra of ZnO / PAN composite nanofiber membrane, PAN nanofiber membrane and PAN powder;

[0023] Figure 4 XRD patterns of ZnO / PAN composite nanofiber membrane, PAN nanofiber membrane and PAN powder;

[0024] Figure 5 The electrical output performance of PAN and ZnO / PAN based PENGs;

[0025] Figure 6 The electrical output stability of ZnO / PAN-based PENG under repeated compression-release cycles;

[0026] Figure 7 The open-circuit voltage before and after rectification generated by the ZnO / PAN-based PENG during walking and running. DETAILED DESCRIPTION

[0027] The present invention provides a method for preparing a ZnO / PAN nanofiber composite piezoelectric material, comprising the following steps:

[0028] The electrospun Zn(Ac)2 / PAN composite nanofiber membrane was subjected to heat treatment and then further hydrothermally grown to obtain a ZnO / PAN nanofiber composite piezoelectric material;

[0029] The preparation process of the ZnO nanorod array includes the decomposition of Zn(Ac)2 and the growth of ZnO nanorods. The temperature of the oven during the heat treatment is 130±5°C and the heat treatment time is 24h. The temperature of the hydrothermal synthesis is 90±5°C and the hydrothermal growth time is 3h. When the temperature of the heat treatment is lower than 130±5°C or the temperature of the hydrothermal synthesis is lower than 90±5°C, the environment of the program heat treatment and hydrothermal synthesis is in a heated state, and the composite nanofiber membrane is avoided from being placed in an oven or growth liquid before reaching a specific treatment temperature.

[0030] In the present invention, unless otherwise specified, all raw material components are commercially available products well known to those skilled in the art.

[0031] In the present invention, the ZnO / PAN nanofiber composite piezoelectric material is preferably obtained by electrospinning and hydrothermal growth of a Zn(Ac)2 / PAN solution. In the present invention, the molecular weight of PAN is preferably 150,000. In the present invention, the mass volume fraction of the Zn(Ac)2 / PAN solution is 15%-20%, more preferably 18%; the solvent in the Zn(Ac)2 / PAN solution preferably includes N,N-dimethylformamide and acetone. In the present invention, the Zn(Ac)2 / PAN solution is preferably prepared under heating conditions. In the present invention, the heating temperature is preferably 40-60°C, more preferably 50°C; the stirring time is preferably 1-24h, preferably 10h; the present invention has no special limitation on the stirring speed, and the stirring speed is sufficient to completely dissolve Zn(Ac)2 / PAN and make the solution uniform and transparent. In the present invention, the working parameters of the electrospinning preferably include: the applied voltage is preferably 15-25V, more preferably 22kV; the flow rate of the Zn(Ac)2 / PAN solution is preferably 0.1-2mL / h, preferably 0.5mL / h, and the electrospinning distance is preferably 5-20cm, more preferably 15cm.

[0032] In the present invention, the preparation process of ZnO nanorod array includes the decomposition of Zn(Ac)2 and the growth of ZnO nanorods. The temperature of the oven during the heat treatment is 130±5°C and the heat treatment time is 24h. The temperature of the hydrothermal synthesis is 90±5°C and the hydrothermal growth time is 3h. When the temperature of the heat treatment is lower than 130±5°C or the temperature of the hydrothermal synthesis is lower than 90±5°C, the environment of the program heat treatment and hydrothermal synthesis is in a warming state, and the composite nanofiber membrane is avoided from being placed in an oven or a growth liquid before reaching a specific treatment temperature. Wherein, the growth liquid is composed of Zn(NO3)2·6H2O, NH3·H2O, HMTA and DI. The concentration of the growth liquid is 30mM, the volume ratio of NH3·H2O is 5%, and the concentration of HMTA is 10mM.

[0033] The present invention provides a ZnO / PAN nanofiber composite piezoelectric material obtained by the preparation method described in the above technical solution. In the present invention, the thickness of the ZnO / PAN nanofiber composite piezoelectric material is about 100±10 μm.

[0034] The present invention provides the application of the ZnO / PAN nanofiber composite piezoelectric material described in the above technical solution in an electromechanical conversion device.

[0035] The present invention provides a flexible piezoelectric nanogenerator based on a ZnO nanofiber composite material, wherein the sandwich structure sequentially comprises a PET insulating layer, a copper metal electrode layer, a ZnO / PAN nanofiber composite piezoelectric material layer, a copper metal electrode layer and a PET insulating layer;

[0036] The material of the nanofiber composite piezoelectric material layer is the ZnO / PAN nanofiber composite piezoelectric material described in the above technical solution.

[0037] The present invention also provides applications of the flexible piezoelectric nanogenerator described in the above technical solution in the fields of medical care, personal thermal management and human activity monitoring.

[0038] Example 1

[0039] An appropriate amount of Zn(Ac)2 was added to a mixed solvent of DMF and acetone (the volume ratio of DMF to acetone was 7:3), and magnetic stirring was performed at room temperature until Zn(Ac) was completely dissolved. Then, PAN powder was added to the mixed solvent to prepare a PAN solution with a concentration of 18wt%, in which the mass ratio of PAN to Zn(Ac)2 was 10:1, and heated and stirred at 50°C for 10h to obtain a uniform and transparent spinning solution. Zn(Ac)2 / PAN nanofiber membrane was prepared using an electrospinning device, and the thickness of the nanofiber membrane was controlled to be about 100μm. The voltage of electrospinning was 22kV, and the flow rate of the spinning solution was 0.5mL·h -1 , the spinning distance is 15 cm.

[0040] Example 2

[0041] The Zn(Ac)2 / PAN and composite nanofiber membranes were placed in an oven at 130°C for heat treatment for 24 hours to decompose Zn(Ac)2 to prepare a ZnO seed layer. ZnO nanorod arrays were grown on a substrate using a hydrothermal synthesis method. The growth solution consisted of 30mM Zn(NO3)2·6H2O, 5% NH3·H2O by volume, 10mM HMTA and DI. The nanofiber membrane containing the ZnO seed layer was placed in the growth solution and sealed, and then placed in an oven at 95°C for hydrothermal growth for 3 hours to prepare ZnO nanorods on a flexible substrate. Finally, the sample with grown ZnO nanorods was rinsed with a large amount of ionized water to remove the residue and dried in air to obtain a ZnO / PAN composite nanofiber membrane.

[0042] Test Example 1

[0043] The microscopic morphology of the fiber membrane before and after the growth of ZnO nanorods was observed by field emission scanning electron microscopy (FE-SEM, Hitachi S4800). The sample was fixed on the sample stage with conductive glue and dried, and the surface of the sample was gold-sprayed by ion sputtering before testing, with a scanning voltage of 10 kV. Figure 2 The microscopic morphology of electrospun PAN nanofiber membrane and ZnO / PAN composite nanofiber membrane is shown. It is not difficult to see from the electron microscope image that the electrospinning technology can produce pure PAN nanofiber membrane with uniform and smooth morphology. From the electron microscope image of the ZnO / PAN composite nanofiber membrane, it can be seen that the ZnO nanorods prepared after heat treatment and hydrothermal growth present a uniform structure and grow along the radial direction of the nanofiber. Since the Zn(Ac)2 / PAN nanofiber membrane floats above the solution after being immersed in the growth solution, the ZnO nanorods on the side in contact with the growth solution grow well, while no ZnO nanorods grow on the other side of the nanofiber membrane.

[0044] Test Example 2

[0045] Infrared spectra of ZnO / PAN composite nanofiber membrane, PAN nanofiber membrane and PAN powder. As can be seen from the figure, ZnO / PAN composite nanofiber membrane, PAN nanofiber membrane and PAN powder all have similar infrared spectra, but the content of planar zigzag conformation is different, and its content can be calculated: the planar zigzag conformation content of ZnO / PAN composite nanofiber membrane is 51.55%, which is higher than that of PAN nanofiber membrane (45.59%) and PAN powder (31.56%). The increase in the content of planar zigzag conformation is attributed to the electrostatic stretching and polarization during the electrospinning process, and the in-situ growth of ZnO nanorods will also increase the content of PAN planar zigzag conformation.

[0046] Test Example 3

[0047] The XRD curves of ZnO / PAN composite nanofiber membrane, PAN nanofiber membrane and PAN powder further proved that there were differences in the molecular conformations of ZnO / PAN composite nanofiber membrane, PAN nanofiber membrane and PAN powder. Compared with PAN powder and PAN nanofiber membrane, the characteristic peak of ZnO / PAN composite nanofiber membrane near 2θ=17° shifted significantly to the right. The content of planar zigzag conformation of ZnO / PAN composite nanofiber membrane was the highest, followed by PAN nanofiber membrane and PAN powder. The preparation of PAN nanofiber membrane by electrospinning and the growth of ZnO nanorods on PAN nanofibers can increase the content of planar zigzag conformation, which is beneficial to the improvement of piezoelectricity of composite membrane.

[0048] Test Example 4

[0049] The open circuit voltages of PAN and ZnO / PAN based piezoelectric nanogenerators were measured. Figure 5 As shown. Under an impact force of 8N at a frequency of about 2Hz, the open circuit voltage of the ZnO / PAN-based PENG is about 6.5V, which is significantly higher than the open circuit voltage of the PAN-based PENG of about 2.4V. Similarly, their output short-circuit currents are also quite different, with the short-circuit currents of the ZnO / PAN and PAN-based PENGs being 2.3μA and 1.0μA, respectively. Compared with the PAN-based PENG, the ZnO / PAN-based PENG has a higher open circuit voltage, and the ZnO / PAN composite nanofiber membrane has better piezoelectric output performance.

[0050] Test Example 5

[0051] The effect of external load resistance on the electrical output of ZnO / PAN-based PENG was tested. The output current of ZnO / PAN-based PENG decreases with the increase of external load resistance, while the output voltage increases with the increase of external load resistance. This experimental result is consistent with Ohm's law. When the external resistance is 1.3MΩ, the maximum output power of ZnO / PAN-based PENG is about 6μW.

[0052] Test Example 6

[0053] In order to prove the electrical output stability of ZnO / PAN-based PENG under long-term operation, the output electrical signals of ZnO / PAN-based PENG were measured after more than 1500 cycles of continuous operation, as shown in Figure 2. Figure 6As shown. Under repeated compression-release cycles, the electrical signal of the ZnO / PAN-based PENG still maintains a stable output, and the output electrical signals of the ZnO / PAN-based PENG at the beginning and end of the measurement are compared in detail. Similarly, the open circuit voltage of the ZnO / PAN-based PENG does not change significantly, indicating that the device can maintain good electrical output characteristics under continuous compression shock. The test results show that the ZnO / PAN-based PENG can not only effectively convert mechanical energy into electrical energy, but also has good output stability, which provides a basic condition for its application in wearable devices.

[0054] Example 3

[0055] The 0.2W heating sheet was integrated with the ZnO / PAN-based PENG through a rectifier bridge and embedded into the insole to prepare a self-powered monitoring insole. The ZnO / PAN-based PENG was used as a wearable power source to power the heating sheet on the sole of the foot.

[0056] Test Example 7

[0057] The prepared self-powered monitoring insole is used as a pressure sensor to distinguish between the two activity states of walking and running (such as Figure 7 As shown in the figure). The voltage recorded during walking is about 7.4V, and the rectified voltage is about 5.9V; while the voltage during running is about 8.2V, and the rectified voltage is 6.7V, and the output voltage signal is more dense. This is because running produces a greater impact force than walking. Due to irregular motion, the output electrical signal of the ZnO / PAN-based PENG is unstable. According to the difference in its output electrical signal, it can be judged whether it is running or walking.

[0058] Test Example 8

[0059] The surface temperature of the two insoles was tested by an infrared thermal imager, and the surface temperature of the insoles was recorded every 10 minutes. The ZnO / PAN-based PENG can effectively convert the mechanical energy of human walking into electrical energy, power the heating sheet on the sole of the foot, and make the heating sheet heat up. Compared with the ordinary insole without the self-powered heating sheet, the temperature of the rear part of the sole of the self-powered monitoring insole is higher than that of the front part of the sole. In addition, under regular exercise (walking) conditions, the surface temperature of the self-powered monitoring insole with the self-powered heating sheet rises faster than that of the ordinary insole. After walking for about 30 minutes, the surface temperature of the self-powered monitoring insole with the self-powered heating sheet tends to be stable, which is 5℃ higher than the surface temperature of the ordinary insole. The PENG based on ZnO / PAN composite nanofibers can be used for personal thermal management and shows great potential in the field of smart wearables.

Claims

1. A method for preparing a ZnO / PAN nanofiber composite material, comprising the following steps: Step 1) Add an appropriate amount of Zn(Ac)2 to a mixed solvent of DMF and acetone (the volume ratio of DMF to acetone is 7:3), and stir magnetically at room temperature until Zn(Ac)2 is completely dissolved. Step 2) adding PAN powder to the mixed solvent of step 1), heating and stirring in a water bath to obtain a uniform and transparent Zn(Ac)2 / PAN spinning solution. Step 3) The Zn(Ac)2 / PAN spinning solution obtained in step 2) is allowed to stand for defoaming, and a Zn(Ac)2 / PAN composite nanofiber membrane is prepared by electrospinning technology. Step 4) The Zn(Ac)2 / PAN composite nanofiber membrane obtained in step 3) is placed in an oven for heat treatment to decompose Zn(Ac)2 to prepare a ZnO seed layer, thereby obtaining a ZnO seed layer / PAN composite nanofiber membrane. Step 5) All samples with ZnO seed layer prepared in step 4) are placed in a growth solution and sealed, and then placed together in an oven for hydrothermal growth to prepare ZnO nanorod arrays on the nanofiber membrane flexible substrate. Step 6) The composite nanofiber membrane grown with ZnO nanorods is rinsed with a large amount of ionized water to remove the residue, and dried in air to obtain a ZnO / PAN composite nanofiber membrane.

2. The method for preparing Zn(Ac)2 / PAN spinning solution according to claim 1, characterized in that: The concentration of PAN solution is 18±0.5wt%, wherein the mass ratio of PAN to Zn(Ac)2 is 10:1, and the solution is heated and stirred at 50°C for 9 to 10 hours.

3. The method for preparing the Zn(Ac)2 / PAN composite nanofiber membrane according to claim 1, characterized in that: The electrospinning voltage was 22 kV and the spinning solution flow rate was 0.5 mL·h -1 , the spinning distance was 15 cm, and the thickness of the Zn(Ac)2 / PAN composite nanofiber membrane was controlled at about 100±10 μm.

4. The method for preparing a ZnO seed layer according to claim 1, characterized in that: The heat treatment temperature of the oven is 130±5℃, and the heat treatment time is 24h.

5. The method for preparing ZnO nanorods according to claim 1, characterized in that: The growth solution consists of 30 mM Zn(NO3)2·6H2O, 5% by volume NH3·H2O, 10 mM HMTA and DI. The hydrothermal growth temperature is 90±5°C and the hydrothermal growth time is 3 h.

6. The ZnO / PAN nanofiber composite piezoelectric material obtained by the preparation method according to any one of claims 1 to 5.

7. Use of the ZnO / PAN nanofiber composite piezoelectric material according to claim 6 in a device for converting mechanical energy into electrical energy.

8. A flexible piezoelectric nanogenerator, characterized in that: The sandwich structure includes a PET insulating layer, a metal electrode layer, a nanofiber composite piezoelectric material layer, a metal electrode layer and a PET insulating layer in sequence.

9. The material of the nanofiber composite piezoelectric material layer is the ZnO / PAN nanofiber composite piezoelectric material according to claim 6.

10. Application of the flexible piezoelectric nanogenerator according to claim 8 in the fields of medical care, personal thermal management and human activity monitoring.

Citation Information

Patent Citations

  • Preparation method of polymer fiber-based ZnO nanowire fiber

    CN106521678A

  • Flexible piezoelectric nanofiber membrane and preparation method and application thereof

    CN108251971A

  • Nanofiber-based flexible array structure electrode and preparation method thereof

    CN109859954A

  • Preparation method of multifunctional all-fiber-based piezoelectric nano generator

    CN114884392A

  • High-temperature-resistant difunctional nano power generation material as well as preparation method and application thereof

    CN118186681A